Usability evaluation of tangible user interfaces for augmented reality - Dias, J. (2003)
This paper presents the usability evaluation results of Mix It, a test bed for authoring in mixed reality environments. While augmented and mixed reality interfaces have been around for a few years, considerable work needs to be done in usability assessment of novel interaction techniques for augmented environments. We have conducted usability evaluations for simple manipulations using simple geometric transformations (translation, rotation, scaling). Even though the results are preliminary and the user group is comparatively small, experimental results proved useful in deriving guidelines and further developments and experimentation with synergistic interaction using multiple modalities.